On the Change of Thematic Openings of Linguistic Journal Articles in Finnish and German - Szurawitzki, Michael (Linguistik Online, 2012)
The article summarizes the main findings of a contrastive and diachronic study of a corpus of 109 Finnish and German thematic openings of linguistic journal articles from the periodicals Virittäjä and Beiträge zur Geschichte der deutschen Sprache und Literatur. The methodology used is based on a modification of Fredrickson/Swales (1994).